The adventures of Huckleberry Finn - Twain, Mark ([London] : Heinle Cengage Learning, 2007)
A nineteenth-century boy, floating down the Mississippi on a raft with a runaway slave, becomes involved with a feuding family, two scoundrels pretending to be royalty, and Tom Sawyer's aunt, who mistakes him for Tom
Title from container
Keywords: Finn, Huckleberry (Fictitious character) -- Fiction; Fugitive slaves -- Fiction; Boys -- Fiction